Management of Portal Vein Thrombosis in Cirrhosis - Stotts, Matthew J.; Wentworth, Brian J.; Northup, Patrick G. (Seminars in Liver Disease, 2021)
While portal vein thrombosis (PVT) is a frequently encountered complication in the cirrhosis population, its management can be challenging for even the most experienced clinicians. Multiple factors must be considered with regards to management, including the degree of underlying portal hypertension and liver dysfunction, risks of therapies including anticoagulation and transjugular intrahepatic portosystemic shunt placement, and extent of the thrombosis. Interpreting the available literature to determine the best treatment strategy for any individual patient can be especially challenging given the lack of prospective, randomized controlled trials and the heterogeneity of cohorts studied. This review will provide an overview of PVT in the cirrhosis population, including necessary steps in evaluation and the potential benefits and drawbacks of different treatment approaches.
Keywords: anticoagulation; TIPS; liver transplantation; mesenteric veins; portal hypertension